The Taxation of Domestic Limited Liability Companies and Limited Partnerships: A Case for Eliminating the Partnership Classification Regulations - Susan Pace Hamill (Washington University Law Quarterly, 1995)
Part II of this Article traces the historical evolution of the entity classification area. Part III then examines how the entity classification regulations have been applied to limited partnerships. Part IV then examines how the classification regulations apply to LLCs, focusing on the guidelines set out in Revenue Procedure 95-10. Finally, in Part V, the Article proposes that the tax policymakers eliminate the use of the partnership classification regulations when determining the taxation of domestic LLCs and limited partnerships.
Keywords: Partnership (Business) – Taxation; Limited partnership; Private companies